Why abandoning the paradise? Stations incentives to reduce gasoline prices at first - Thomas Wein (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2020)
The German petrol station market is characterized by strong intraday price cycles, which probably correspond to the well-known Edgeworth cycles. The prices go up strongly in the late evening or in the middle of the night, fall relatively heavily in the early morning and then go up and down several times in the course of the day. Locally, the analysis is limited to the 26 petrol stations that plausibly form a common market in the Lueneburg region. This essay picks out the specific sequence in which, after generally rising prices during the day, a single supplier is the first to reverse the price trend and lower its price. For this purpose, current price reports are used to define the price reduction event down to the second, and to show only the valid prices of competitors prior to the event. All German petrol stations have to report price changes to the Bundeskartellamt's Market Transparency Department. Tankerkoenig then publishes the full reports. This results in one panel observation for each price reduction event. Out of nearly 300,000 price observations, just over 10,000 panel observations result. Fixed-effect logit estimates are used to test whether the theoretically and economically significant price differences of the Edgeworth cycles explain the behavior of the price cutters, or whether market structure factors, such as brand affiliation/independence of the petrol station, service offerings, or location characteristics predict price-cutting behavior. The novel recording of the price dynamics in the petrol station market by using the accurate petrol station price data to the second indicates promising research of extensive price data and avoids the enormous loss of information in the previously common calculation of average prices at certain times.
Keywords: L13; L41; K21; 330; Edgeworth cycles; gasoline prices; dynamic pricing